Penerapan Sistem Informasi Geografis dan AHP Untuk Klasifikasi Masyarakat - Supriyono, Supriyono; Mustafid, Mustafid; Sugiharto, Aris (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
Geographic  information  system  useful  to the  government's  classifications  to  determine  the priority of the  welfare of  society.  While  the criteria  used  are  6  criteria  and  14  sub  criteria  and  their  implementation  is  still  done  by  manual.  The  method  used  in  the  study  "The implementation  of  Geographic  Information  Systems  and  AHP  for  Village-Based  Economic  Classification  Society"  is  the  method  ofAnalytical  Hierarchy  Process  (AHP)  in  which  the  classification  process  conducted  by  the  preparation  of  the  hierarchy,  giving  the comparative value of each criterion to determine the value of the criteria. As for the mapping process using Quantumgis and MSAW 3.0. Quantumgis  and  MSAW  3.0  is used  because  both applications  are  open source applications  that  can  be used  without having  to pay  fortheir use. The results of the application system that can be used to make the process of classification societies where the determination ofcriteria  and  sub  criteria  can  be changed  in accordance  with  the  desired  indicator.  Results  included  as  data  calculation  and  classificationwith the City district map can be made a map of economic classification society in City districtKeywords: Geographic information systems; AHP; Economic; Classification society.